Кто-то следит за мной: роман / В. Готти ; пер. с англ. В. А. Вебер - Готти Виктория (Клуб XXI век, 2000)
Экземпляры: аб. (2009) / Инвентарный номер: 52703 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Г 74 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44